Meningkatkan Kesadaran Lingkungan Melalui Konservasi Penyu dan Mangrove di Pantai Malang Selatan: Pengabdian - Mochammad Rozikin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sea turtle and mangrove conservation play a strategic role in maitaining the balance of coastal ecosystem. A community service program themed on sea turtle and mangrove conservation was conducted at Bajulmati Beach and Ungapan Beach, Malang Regency, in collaboration with the Bajulmati Sea Turtle Conservation. The aim of this program was to raise students’ awareness of the importance of preserving coastal environments. The participants were provided with education on sea turtle and mangrove conservaion and were actively involved releasing 196 hatchlings into their natural habitat and planting 75 mangrove seedlings along the riverbanks. A total of 150 students form Universitas Brawijaya participated in this program, gaining insights into the critical role of sea turtles and mangroves in maintaining marine esosystem balance. The program’s outcomes showed an increased awareness among student about the significane of conservation and the sustainability of coastal ecosystems. It hoped that students will develop a stronger sense of responsibility in protecting the environtment and contributing to conservation efforts in the futur. Furthermore, this program aims to foster ecological awareness among the younger generation as future stewards of natural resources.